Applying a research ethics model to the practice of being a strength and conditioning coach - Meir, R.; Nicholls, A. R. (Strength and Conditioning Journal, 2018)
The strength and conditioning (s&c) coach's role could be described as being similar to other allied health professionals (e.g., physical therapists, physio-therapists, and sports physicians) who provide a service to a client-either individual athlete or team. Such a relationship should be based on respect, mutual responsibility, and ethical equality. To this end, there should be an expectation, from the athlete, that the s&c coach will be developing training programs that conform to some model of good ethical practice. This article presents a model that can be used by the s&c professional to guide their ethical practice.